COMMUNITY DEVELOPMENT: The Medina Community as the Ideal Prototype of Community Development - Badrah Uyuni; Muhibudin Muhibudin (Spektra: Jurnal Ilmu-ilmu Sosial, 2020)
Community development da'wah is a social change planning process based on Islamic values. The target for community development is, therefore, to the social setting of community life, rather than individual by individual. In realizing a legal welfare state as intended by the Qur'an, namely a prosperous state under the auspices of Allah, the Almighty, the state is obliged to regulate and allocate sufficient funds for the purposes of guaranteeing the people who need it. Social security includes unemployment benefits, parental benefits (retirement age), scholarships for those who are studying and others. The state is also obliged to provide facilities for worship, education, orphanages, hospitals and others. In the state of Medina law, there is only one motivation for the welfare principle, namely the Islamic doctrine: hablun min Allah wa hablun min al-nas, namely aspects of worship and aspects of muamalah. The realization of the principle of the welfare state law is solely aimed at realizing social justice in society in accordance with the commands of Allah SWT. The Medina community that was built by the Prophet Muhammad, SAW is a society that has succeeded in enforcing the values ​​of justice, the principle of legal equality, guaranteeing welfare for all citizens, and protecting minority groups. Muslim thinkers regard the people (city) of Medina as a prototype of the ideal society of Islamic products. This is based on the hadith of the Prophet Muhammad, SAW in his saying, "There is no society in this world that is as good as society, or the best of times is my time."